ASSESSING THE INFLUENCE OF STRATEGIC PLANNING ON WORK-LIFE BALANCE AMONG EMPLOYEES AT AL-HIKMAH UNIVERSITY ILORIN - Oladimeji, Rasheedat Modupe (Universitas Ratu Samban, 2024)
This study explores the influence of strategic planning on work-life balance among employees at Al-Hikmah University in Ilorin, Nigeria. As higher education institutions face increasing demands for productivity and excellence, understanding the interplay between organisational strategies and employee well-being has become critical. The sample size was 110 employees and descriptive statistics and inferential statistical techniques were used to analyse the data. A structured questionnaire was used to collect data, focusing on perceptions of strategic planning and work-life balance. The findings revealed a significant correlation between effective strategic planning and improved work-life balance, emphasising the importance of transparency, inclusivity, and employee engagement in planning processes. Furthermore, the research highlights the impact of organisational culture on the implementation of strategic initiatives, suggesting that a supportive environment is essential for fostering employee satisfaction and retention. It found that transparent and inclusive strategic planning processes lead to a positive work-life balance, fostering a sense of ownership and commitment. The study also highlighted the importance of organisational culture in implementing effective policies. The research emphasises the need for continuous evaluation and adaptation of strategic initiatives to ensure they remain relevant and effective. This study contributes to the existing literature by addressing a notable gap in research regarding the connection between strategic planning and employee well-being in Nigerian higher education. It was recommended among others that creating structured opportunities for employees to participate in the strategic planning process can foster an organisational culture that prioritises employee well-being.